Microware Review - Len Proctor (The Canadian Network for Innovation in Education (CNIE), 1996)
SoundEdit makes it possible to record and edit music and voice, add special effects like echo or reverb to the soundtrack, analyse the results and compress the final sound track to reduce file storage space requirements. SoundEdit literally turns your computer into a sound recording studio.